Post‐release survival of shortfin mako (Isurus oxyrinchus) and silky (Carcharhinus falciformis) sharks released from pelagic tuna longlines in the Pacific Ocean. Issue 4 (27th February 2023) - Francis, Malcolm P.; Lyon, Warrick S.; Clarke, Shelley C.; Finucci, Brittany; Hutchinson, Melanie R.; Campana, Steven E.; Musyl, Michael K.; Schaefer, Kurt M.; Hoyle, Simon D.; Peatman, Tom; Bernal, Diego; Bigelow, Keith; et al.
Abstract: Substantial global population declines in pelagic sharks have led to the introduction of management and conservation measures, including gear restrictions and no‐retention policies, to curb declines and encourage stock recovery. As the rate of discarding sharks increases, there is a growing need to understand prognostic factors that influence their post‐release survival (PRS) outcomes. PRS was measured with survival pop‐up satellite archival tags attached to shortfin mako ( Isurus oxyrinchus ) and silky sharks ( Carcharhinus falciformis ) released or discarded from pelagic tuna longline fishing vessels operating in the Western and Central Pacific Fisheries Commission Convention Area. In total, 117 tags were deployed on 60 mako and 57 silky sharks captured as bycatch during commercial pelagic longline fishing trips in New Zealand ( n = 35), Fiji ( n = 58), New Caledonia ( n = 10) and the Republic of the Marshall Islands ( n = 14). Mako engaged in long‐distance movements between New Zealand, Australia, Fiji and New Caledonia, while silky sharks tagged in the Marshall Islands showed evidence of seasonal movements eastward. PRS was determined for 110 sharks (57 mako, 53 silky sharks). Most tagged sharks of both species were uninjured (89%) at capture and most sharks (88%) survived post‐release until tag loss or the programmed pop‐up date (60 days). However, when considering a complete fishing interaction (haulback, handling, release), PRS estimates were markedly reduced to 48.6% and 52.3% for mako and silky sharks, respectively. For both species, survivorship was greater in large (>150 cm fork length) uninjured sharks and sharks released with low shark length to trailing branchline ratios. While these findings suggest that retention bans offer sharks an increased chance of survival, continued efforts should be made to improve handling and release practices, reduce trailing gear and minimize pelagic shark bycatch.